EXAMINING THE IMPACT OF USING LEARNING MEDIA ON STUDENTS’ LEARNING MOTIVATION AND LEARNING OUTCOMES - Permatasari, Romadina; Suarman, Suarman; Gimin, Gimin (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2024)
This research aims to examine the influence of the use of learning media on students’ learning motivation and learning outcomes in creative economics courses at an education department of one university in Indonesia. The research was carried out employing a quantitative approach with descriptive research methods. The population of this research is undergraduate students from three classes (2019 -2021 cohorts) at this department with a total population of 232 students. They were selected using the Simple Random Sampling method so that the number of samples taken was 70 students. Data were collected using a questionnaire which was distributed to respondents via the Google Form. Data analysis was carried out using regression analysis with the path analysis method to test the research hypothesis. This study found that: 1) the use of learning media has a positive effect on students’ learning motivation; 2) learning motivation has a positive effect on students’ learning outcomes; 3) the use of learning media has a positive effect on students’ learning outcomes (with learning motivation as a mediator). These findings imply that the use of learning media is highly recommended for improving students’ learning outcomes. This influence becomes greater when learning motivation is used as a mediator. This study also shows that learning motivation acts as an intermediary between the use of learning media and students’ outcomes